Overexpression of programmed cell death ligand 1 in patients with CIN and its correlation with human papillomavirus infection and CIN persistence - Sancakli Usta, Ceyda (Infect Agent Cancer, 2020)
BACKROUND: HPV causes specific cell-mediated immunity in the cervix. Mononuclear cells such as helper T cells (CD4+), cytotoxic T cells (CD8+), and dendritic cells play a critical role in the initiation of the HPV-specific immune response and destruction of virus-infected cervical epithelial cells. The programmed cell death ligand 1 (PD-L1) gene encodes an immune inhibitory receptor ligand and overexpression of PD-L1 inhibits T-cell activation and cytokine production. The aim of this study was to investigate the expression of PD-L1 in cervical tissue and its correlation with clinicopathological findings. METHODS: In this cross-sectional study, a total of 94 women who were referred for colposcopy due to abnormal Papanicolaou (PAP) test results and/or HPV positivity were evaluated. The presence of HR-HPV–DNA was analyzed using type- and gene-specific primers along with commercial real-time polymerase chain reaction. The cervical examination was done with a colposcope. Cervical biopsies were obtained from the areas that were evaluated as abnormal during the colposcopy. Histopathological result of cervical biopsies were defined as no intraepithelial neoplasia (CIN 0), mild CIN (CIN I), and moderate-to-high CIN (CIN II-III). All women were classified into four groups based on their HR-HPV positivity and cervical biopsy results: Group I (controls; n = 29), HR-HPV (−) CIN 0; Group II (n = 21), HR-HPV (+) CIN 0; Group III (n = 20), HR-HPV (+) CIN I; and Group IV (n = 24), HR-HPV (+) CIN II-III. A semi-quantitative scoring system was used to evaluate the degree of Ki-67, p16, and PD-L1 immunoreactivity in the cervical tissue samples. RESULTS: We found that PD-L1 expression in both mononuclear cells and in cervical epithelial cells gradually increases from the HR-HPV (−), CIN 0 group to the HR-HPV (+), CIN II-III group (p = 0.0003 and p = 0.0394, respectively) and mononuclear PD-L1 expression was correlated with HPV type, initial Pap test results, HPV persistence, and CIN persistence or recurrence (p = 0.0180, p = 0.0109, p = 0.0042, and p = 0.0189, respectively). Moreover, mononuclear PD-L1 expression was also correlated with Ki-67 and p16 immunoreactivity (p = 0.0432 and p = 0.0166, respectively). Epithelial PD-L1 expression was only correlated with HPV type and the presence of HPV persistence (p = 0.0122 and p = 0.0292, respectively). CONCLUSION: During the initial evaluation of the cervical histology results, the assessment of PD-L1 expression—especially in mononuclear cells in cervical tissue samples—may provide more information on the progression of HR-HPV infection and its persistence.